Carboplatin-resistance-related DNA damage repair prognostic gene signature and its association with immune infiltration in breast cancer - Dong, Shuwen; Li, Anqi; Pan, Ruixin; Hong, Jin; Wang, Zheng; Shen, Kunwei (Frontiers in Immunology, 2025)
IntroductionBreast cancer is among the most prevalent malignant tumors globally, with carboplatin serving as a standard treatment option. However, resistance often compromises its efficacy. DNA damage repair (DDR) pathways are crucial in determining responses to treatment and are also associated with immune infiltration. This study aimed to identify the DDR genes involved in carboplatin resistance and to elucidate their effects on prognosis, immune infiltration, and drug sensitivity in breast cancer patients.MethodsA 3D-culture model resistant to carboplatin was constructed and sequenced. Co-expressed DDR genes were analyzed to develop a predictive model. Immune infiltration analysis tools were employed to assess the immune microenvironment of patients with varying expression levels of these risk genes. Additionally, drug sensitivity predictions were made to evaluate the efficacy of other DNA damage-related drugs across different risk groups. Molecular assays were performed to investigate the role of the key gene TONSL in breast cancer.ResultsBy integrating data from public database, we established a prognostic signature comprising thirteen DDR genes. Our analysis indicated that this model is associated with immune infiltration patterns in breast cancer patients, particularly concerning CD8+ T cells and NK cells. Additionally, it demonstrated a significant correlation with sensitivity to other DDR-related drugs, suggesting its potential as a biomarker for treatment efficacy. Compared to the control group, TONSL-knockdown cell lines exhibited a diminished response to DNA-damaging agents, marked by a notable increase in DNA damage levels and enhanced drug sensitivity. Furthermore, single-cell analysis revealed elevated TONSL expression in dendritic and epithelial cells, particularly in triple-negative breast cancers.ConclusionsCarboplatin resistance-related DDR genes are associated with prognosis, immune infiltration, and drug sensitivity in breast cancer patients. TONSL may serve as a potential therapeutic target for breast cancer, particularly in triple-negative breast cancer, indicating new treatment strategies for these patients.